Impact of Enterprise Risk Management on the Performance of the Publicly Listed Companies on London Stock Exchange - Enkhbaatar, Ider (2019)
This dissertation studies the relationship between the implementation of Enterprise Risk Management (ERM) and Business and Market performance of listed companies in London Stock Exchange from 2012 to 2018. Based on the selected sample, it is found that the implementation of ERM does not increase shareholders value, instead it has a negative impact on business performance. Particularly, the presence of Chief Risk Officer, size of Risk Committee, the number of non-executive directors had negative effect on ROA for the whole sample. Therefore, this study provides further investigation by classifying sample as financial and non-financial industry. Therefore, more negative effects found in financial industry and no evidence of relationship found in non-financial industry. However, there was no statistically significant relationship found between ERM implementation and market performance. This dissertation makes contribution to the empirical evidences on ERM studies. The findings raises a question whether the ERM is truly implemented in the UK during the reported period or companies claim to have implemented ERM as it is becoming more and more common method. This demonstrates a necessity for further research on this topic.